Amphiregulin Induces iNOS and COX-2 Expression through NF-κB and MAPK Signaling in Hepatic Inflammation - Yu Jung Heo; Nami Lee; Sung-E. Choi; Ja Young Jeon; Seung Jin Han; Dae Jung Kim; Yup Kang; Kwan Woo Lee; Hae Jin Kim (Hindawi Limited, 2023)
Background. Inflammation is a major cause of hepatic tissue damage and accelerates the progression of nonalcoholic fatty liver disease (NAFLD). Amphiregulin (AREG), an epidermal growth factor receptor ligand, is associated with human liver cirrhosis and hepatocellular carcinoma. We aimed to investigate the effects of AREG on hepatic inflammation during NAFLD progression, in vivo and in vitro. Methods. AREG gene expression was measured in the liver of mice fed a methionine choline-deficient (MCD) diet for 2 weeks. We evaluated inflammatory mediators and signaling pathways in HepG2 cells after stimulation with AREG. Nitric oxide (NO), prostaglandin E2 (PGE2), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) were analyzed using an enzyme-linked immunosorbent assay and western blotting. Nuclear transcription factor kappa-B (NF-κB) and mitogen-activated protein kinases (MAPKs), including extracellular signal-regulated kinase, c-Jun N-terminal kinase, and p38 mitogen-activated protein kinase, were analyzed using western blotting. Results. Proinflammatory cytokines (interleukin (IL)-6, IL-1β, and IL-8) and immune cell recruitment (as indicated by L3T4, F4/80, and ly6G mRNA expression) increased, and expression of AREG increased in the liver of mice fed the MCD diet. AREG significantly increased the expression of IL-6 and IL-1β and the production of NO, PGE2, and IL-8 in HepG2 cells. It also activated the protein expression of iNOS and COX-2. AREG-activated NF-κB and MAPKs signaling, and together with NF-κB and MAPKs inhibitors, AREG significantly reduced the protein expression of iNOS and COX-2. Conclusion. AREG plays a role in hepatic inflammation by increasing iNOS and COX-2 expression via NF-κB and MAPKs signaling.